Difficulties faced by students of the third year of the Licenciatura en Idioma Inglés opción Enseñanza in the Foreign Language Department of the University of El Salvador in the process of developing their grammatical competence and the actions they take to overcome them - Amaya Fuentes, Belinda Soledad (2024)
the third year of the Licenciatura en Idioma inglés Opción Enseñanza in the Department of Foreign Languages of the University of El Salvador face during the process of developing their grammatical competence. In this sense the essay will present the reasons why students consider grammatical competence one of the most difficult abilities to develop in the process of acquiring or learning the English language.This will be an argumentative essay, and based on the information gathered from different authors, teachers and students themselves. It will expose the real reasons why students have so many difficulties to get grammatical competence in English. In addition to this, the essay will provide a set of ideas intended to be useful for teachers and students in the teaching and learning process of the English language. The information provided in this essay will specifically help teachers and students with the issues they come across when teaching or learning the English language. Difficulties Faced by Students of the Third Year of the Licenciatura En Idioma Inglés Opción Enseñanza in the Foreign Language Department of the University of El Salvador in the Process of Developing their Grammatical Competence and the Actions they Take to Overcome them In the process of learning English as a second or foreign language, students see themselves facing different kinds of problems regarding the different skills they are to possess in order to master the language. One of the most common difficulties students of the English language face is the development of their grammatical competence, which is vital and of great importance due to the nature of the career. Students of the Foreign Language Department at the University of El Salvador believe the development of grammatical competence is one of the most difficult issues and yet very important in the process of learning English